Classification of Disaster Risk Areas on Mount Ruang Using Vegetation Index Calculations and Landsat-8 Satellite Imagery - Siti Zainab; M. Abhiel Laits Qatadah; Fithri Estikhamah; Minarni Nur Trilita (Future Science, 2024)
Mount Ruang is located in Tagulandang District, Siau Tagulandang Biaro Islands Regency, North Sulawesi, with an elevation of 725 meters or 2,379 feet, at coordinates 2°18' N / 125°22' E. In April 2024, a significant eruption was re-recorded. Ruang Island is the peak of the volcano rising from the Sulawesi Sea. Most of its inhabitants are farmers, and land use in an area is influenced by population growth and activities. The eruption of Mount Ruang has caused changes in land function. In this study, classification was conducted using the Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI). The data were sourced from Landsat 8 imagery from 2022 to 2024, specifically bands 4 and 5. The results of this study conclude that from 2022 to 2024, the vegetation index calculations were very significant. Classification calculations before and after the eruption showed that the NDVI vegetation index in 2022 and 2023 indicated vegetated land, while in 2024, it indicated non-vegetated land. The SAVI vegetation index identified water bodies such as rivers or seas. It can be concluded that post-eruption, the land around the volcano was non-vegetated and much of the material fell into the sea.